PENGARUH KOMUNIKASI DAN KERJASAMA KELOMPOK TERHADAP KINERJA KARYAWAN PADA ASIALINK HOTEL BY PRASANTHI BATAM - Elia; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2022)
Human resources are needed in company's operational activities for achieving company’s goals. Employees assessment can be seen from their performance. Qualified employees can achieved the expected goals. This research aims to examine influence of communication and teamwork on employee performance at Asialink Hotel by Prasanthi Batam partially or simultaneously. Descriptive research design was determined using a quantitative approach. Data management and analysis tool used SPSS version 25. Sampling technique used saturated sampling, including all employees with total sample 104 respondents. Data collection using questionnaires via google form. Testing data using validity and reliability test. Classical assumption test using normality test, multicollinearity test and heteroscedasticity test. Influence test using multiple linear regression analysis and coefficient determination analysis. Hypothesis testing using T test and F test. According to the results of statistical testing, variables of communication, teamwork and employee performance are normally distributed, the independent variables do not occur multicollinearity and heteroscedasticity. Results of the coefficient determination indicate that communication and teamwork have an effect of 33.8% on employee performance, while the rest is influenced by other variables. The conclusion from the results is simultaneously communication and teamwork variable has a significant effect on employee performance.